Radiological Aspects of HR-CT Scan on Temporal Bone - Ferriastuti, Widiana; Ramayuda, Ida Bagus (Folia Medica Indonesiana, 2022)
Highlight: • High-resolution computed tomography (HRCT) scan has advantage for best image reconstruction and informative in interpreting images of the temporal bone. • The essential primary aspect in HRCT of the temporal bone scan is technique and protocol. Abstract: The high-resolution computed tomography (HRCT) scan used in the 1980s offers a distinct advantage in interpreting images of the temporal bone. To obtain a right image reconstruction and to provide meaningful information, a certain degree of tilt is required so that radiologists and clinicians can get more real imaging information on structural abnormalities in the temporal bone and its soft tissue constituents. The technique or protocol in HRCT of the temporal bone becomes an essential primary aspect in presenting the analyzed structure, the assessment of the small form of the auditory bones, the soft tissue of the inner ear and the cranial nerves that pass through the temporal bone structure is much easier to analyze, of course with the help of reconstruction according to the HRCT protocol for temporal bone, however, soft tissue evaluation is preferable to MRI. In the end, the standard structure, congenital abnormalities and pathological problems in the temporal bone structure can be identified and informed to the clinician as a step to determine further treatment action.